Enactment of a Translingual Approach to Writing. Issue 2 (16th July 2020) - Sun, Yachao; Lan, Ge
Abstract : With increasing interest in a translingual approach to writing studies, a considerable amount of empirical research has been conducted to investigate how this approach can affect writing practice and pedagogy. This article reports on 42 empirical studies on a translingual approach to writing and discusses the approach's implications for teaching writing in English as an additional language (EAL). The results reveal that a translingual approach has been enacted in various contexts with diverse writer groups and for different research foci. The findings show that a translingual approach that advocates for writer agency, languages other than English as resources rather than impediments, heterogeneity as the norm in the classroom, and a challenge to English monolingualism (1) brings more ideological discussions to the teaching of EAL writing, (2) enriches written feedback studies with more negotiation of unconventional language use, and (3) facilitates EAL writing instruction and learning through viewing oral genres as resources for written genres. Nevertheless, the findings also indicate the need for caution (such as balancing language norms and deviations rather than resisting the norms and crossing rather than flattening language differences) in adopting a translingual approach to EAL writing. Abstract :